Beyond action: applying consequentialism to decision making and motivation - Ord, T (2009)
It is often said that there are three great traditions of normative ethics: consequentialism, deontology, and virtue ethics. Each is based around a compelling intuition about the nature of ethics: that what is ultimately important is that we produce the best possible outcome, that ethics is a system of rules which govern our behaviour, and that ethics is about living a life that instantiates the virtues, such as honesty, compassion and loyalty. This essay is about how best to interpret consequentialism. I show that if we take consequentialism beyond the assessment of acts, using a consequentialist criterion to assess decision making, motivation, and character, then the resulting theory can also capture many of the intuitions about systems of moral rules and excellences of character that lead people to deontology and virtue ethics.